PENGEMBANGAN BAHAN AJAR MATERI PETA TOPOGRAFI UNTUK EKSTRAKULIKULER PANDU HIZBUL WATHAN - Karlita, Dea, Drs. Muhammad Musiyam, MTP (2015)
Map is the once of the learning media which had necessary contribute to increase the learning quality in school, specially social knowledgement. This far, the usage of the map isnt interesting for student, only memorize step, and unreach the logicly step. According by the condition, increasing the map understanding by the areas close probably create the logicly meaning, its because the areas closes could deeply combining the life aspect and the uniqueses that lifes aspect and the uniqueses that exist in the area also could create the setted understanding about problem as teritorial. The reserch subjects area the scouts organization student in SMA Muhammadiyah 1 Surakarta. The experiment model which use is one group pretest and posttest compare the material that which after and before its developed